Algorithms in the lower secondary school: Why and how to teach them in mathematics class? - Lupunen, Veera (LUMAT-B: International Journal on Math, Science and Technology Education, 2022)
In this article the concept of algorithm and how algorithms could be teached in the Finnish lower secondary school is studied. Algorithms are sets of rules that have certain properties such as finiteness and effectiveness. Computational thinking is a thought process where the purpose is to find a solution to a computational problem which can be solved by using an algorithm. The Finnish National Curriculum for the Lower Secondary School (grades 7–9) outlines the learning objectives as developing computational thinking and achieving programming skills. The LUMATIKKA course Developing Computational Thinking aims to support teachers in teaching these subjects and learning more about algorithms themselves. The course also provides practical ideas for teaching. Computational thinking can be developed by learning about algorithms and knowing them is also a part of general knowledge of today. Additionally, teaching algorithms in the lower secondary school supports many of the aims of teaching mathematics.